The “Sound of Silence” in a Neonatal Intensive Care Unit—Listening to Speech and Music Inside an Incubator - Bertsch, Matthias; Reuter, Christoph; Czedik-Eysenberg, Isabella; Berger, Angelika; Olischar, Monika; Bartha-Doering, Lisa; Giordano, Vito (Frontiers in Psychology, 2020)
Background: The intrauterine hearing experience differs from the extrauterine hearing exposure within a neonatal intensive care unit (NICU) setting. Also, the listening experience of a neonate drastically differs from that of an adult. Several studies have documented that the sound level within a NICU exceeds the recommended threshold by far, possibly related to hearing loss thereafter. The aim of this study was, firstly, to precisely define the dynamics of sounds within an incubator and, secondly, to give clinicians and caregivers an idea about what can be heard “inside the box.” Methods: Audio recordings within an incubator were conducted at the Pediatric Simulation Center of the Medical University Vienna. They contained recorded music, speech and synthesized sounds. To understand the dynamics of sounds around and within the incubator the following stimuli were used: broadband noise with decreasing sound level in ten steps of 6 dB, sine waves (62.5, 125, 250, 500, 1000, 2000, 4000, 8000 and 16000 Hz), logarithmic sweep (Chirp) over the frequency band 20 Hz to 21 kHz, singing male voice, singing and whispering female voice. Results: Our results confirm a protective effect of the incubator from noises above 500 Hz in conditions of “no-flow” and show almost no protective effect of an incubator cover. We, furthermore, observed a strong boost of low frequencies below 125 Hz within the incubator, as well as a notable increase of higher frequency noises with open access doors, a significant resonant effect of the incubator, and a considerable masking effect of the respiratory support against any other source of noise or sound stimulation even for “low-flow” conditions. Conclusion: Our study reveals high noise levels of air supply at high flow rates and the boost of low frequencies within the incubator. Education of medical staff and family members as well as modifications of the physical environment should aim at reducing noise exposure of preterm infants in the incubator. Audiovisual material is provided as supplementary material.